Peran Teknologi dalam Prestasi Akademik Siswa: Tinjauan Literatur - Malik Nur, Imam Dedikasi; Yoenanto, Nono Hery; Andriani, Fitri (Perspektif Ilmu Pendidikan, 2025)
The rapid advancement of technology, including Virtual Reality (VR), Augmented Reality (AR), metaverse, Learning Analytics (LA), and digital formative assessment (DFA), presents mixed findings regarding their impact on student academic achievement. The variability ranging from the consistently positive effects of VR/AR in enhancing spatial reasoning and motivation to the inconsistent effectiveness of LA interventions necessitates an urgent synthesis of the current evidence. Therefore, this study aimed to explore and map the most recent empirical evidence (2016–2025) on the role of these technologies in improving student academic outcomes, participation, and cognitive development. Employing a scoping review methodology following PRISMA-ScR guidelines, this review systematically analyzed 13 primary empirical studies selected from the Scopus and Web of Science databases. The results indicate that the majority of studies (12 out of 13) report a significant increase in academic performance. Immersive technologies were particularly prominent due to their ability to reduce cognitive load and significantly boost student motivation and self-efficacy through embodiment, aligning with the theoretical frameworks of Cognitive Load Theory (CLT) and the Cognitive Affective Model of Immersive Learning (CAMIL). However, the effectiveness of interventions like LA was found to be conditional and inconsistent, highlighting that pedagogical design and feedback quality are more crucial determinants of success than the technology itself. The main conclusion is that technology's benefits depend critically on careful pedagogical implementation; consequently, the focus must shift from whether technology is used to how it is effectively integrated to ensure maximum knowledge transfer.